Program Kampung Keluarga Berencana Menurut Hukum Islam - Nur Lailatul Musyafaah (State Islamic University (UIN) of Sunan Ampel, 2018)
The KB village has several programs, namely Family Planning (KB), Tribina which includes Family Development Coaching, Adolescent Family Development, Elderly Family Development (BKB, BKR, and BKL), Efforts to Increase Prosperous Family Income (UPPKS), and Information and Counseling Center Youth (PIK_RM). Based on the analysis of Islamic law, the Family Planning Village program in general is in accordance with the principles of Islamic law, but there are a number of programs whose laws are disputed by Jurisprudence. The Tribina program is in accordance with Islamic law, because the obligation of parents to care for and educate their children from toddlers to adolescents is good, and caring for elderly parents is an obligation of children to their parents. Regarding the family planning program, the majority of scholars allow for the use of contraceptives not to be permanent, not harmful and carried out by experts, while the permanent contraception, such as vasectomy and tubectomy, the majority of scholars forbid them. In connection with the UUPKS, the legal UUPKS may even be recommended because part of mutual assistance. But what needs to be considered is that the business must be in accordance with the concept of Islamic business, including not containing elements of gharar (uncertainty) and usury. The PIK_RM is in accordance with Islamic law, because fostering teenagers with proper and good guidance is highly recommended in Islamic law, so that they can become a superior generation and not fall into bad things.